PKMS Peningkatan Produktivitas IRT Kelompok Budidaya Bebek Desa Sei Mencirim Kabupaten Deli Serdang - Iswandi Idris; Ruri Aditya Sari; Zubaidah Hamum (Journal of Social Responsibility Projects by Higher Education Forum, 2020)
PKMS target partners are community groups with a type of economic productive partner named Bebek Barokah led by Mrs. Masri Yuni, the number of group members is 3 people. Partner problems, namely marketing and production problems. The agreed issues to be addressed are: Increased egg production, marketing promotion, salted egg production and business management. The training is carried out both theoretically and practically with expert sources through lectures, questions and answers, discussions and exercises, monitoring and mentoring. The indicators for the success of this PKM are: Publications in National Journals, Publications in printed mass media, Videos of activity implementation, Increased empowerment of partners - increased partner turnover. PKMS location is about ± 22 KM from the LP3I Medan Polytechnic campus, namely Jl. Tiger Gg. Ubi Pasar I Dusun IX Sei Mencirim Kec. Sunggal Kab. Deli Serdang. PKMS results show that the economic impact of partner groups has increased, productivity has also increased. The partner group has knowledge regarding alternative raw materials, the use of technology and an understanding of good feed processing and procedures. The partner group has increased skills in processing and producing salted eggs